Bimbingan Rohani Islam Untuk Meningkatkan Efikasi Diri Santri; Studi Kasus Layanan Pendidikan Pesantren Krapyak Yogyakarta - Fauziya Rohmah; Nurus Sa'adah (TA'DIB: Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyze spiritual guidance in increasing the self-efficacy of students in Islamic boarding schools. In the context of Islamic boarding schools, students' self-efficacy has an important role in building balanced character and personal development. This must be seen holistically that self-efficacy is a belief possessed by individuals to have the ability to manage and perform actions in order to achieve certain goals, while Islamic spiritual guidance itself is a process of conveying Islamic values ​​to someone carried out by spiritual mentors so that they can strengthen faith and soul. Therefore the method of spiritual guidance becomes necessary in implementing psychological self-efficacy improvements, especially for students who live in Islamic boarding schools. The focus of the research carried out is the method in Islamic spiritual guidance, two methods are carried out (1) the direct method; (2) indirect method. This type of research uses descriptive qualitative research. Sampling used purposive sampling, while the data collection technique used was in-depth interviews, observation and documentation. The research was conducted at the Islamic boarding school Al-Munawwir Krapyak Yogyakarta with the results showing that spiritual guidance service methods can improve students' self-efficacy.